Theoretical and experimental research of bearing capacity and fatigue life for coiled tubing under internal pressure. (October 2019) - Shaohu, Liu; Feng, Guan; Xianjin, Wu; Hui, Xiao; Zhen, Wang; Ting, Yang
Abstract: Coiled tubing (CT) endures high pressure during operation, thus causing high possibility of fatigue failure. Firstly CT's failure under high pressure and effects of pressure on CT fatigue life were investigated. Based on classical elastic mechanics theory, the CT ultimate internal pressure theoretical model was established. Based on classical plasticity stress computational formulas, the CT fatigue life theoretical model was established. Experimental research of internal pressure's effect on CT fatigue life was carried out. The theoretical calculation result is proven to be in good agreement with experimental data of fatigue cycle time under different pressure. The results show that internal pressure is one of the main influential factors on CT's bearing capacity, and that CT is exceedingly easy to have fatigue failure under internal pressure. The result validates the feasibility of CT ultimate internal pressure theoretical model and fatigue life model. The fatigue life of CT decreases with the increase of CT internal pressure. It is suggested to use CT with high strength and low inner-to-outer diameter ratio when working with high internal pressure. Study of internal pressure effects on CT bearing capacity and fatigue life can be used as a reference for the pressure control and safe operation of CT on field. Highlights: The theoretical model of CT ultimate internal pressure was established. The theoretical model of CT fatigue life was established. Experimental research of CT fatigue life was carried out under internal pressure.